IMPLEMENTATION OF DHIKR THERAPY FOR MENTAL DISORDERS WITH SENSORY PERCEPTION DISTURBANCE NURSING PROBLEMS AT CANDIPURO COMMUNITY HEALTH CENTER - Rahmawati, Primasari Mahardhika; Abidin, Zainal; Puji Astutik, Devi (Journal of Vocational Nursing, 2025)
Introduction: Mental disorders are a serious health issue that can significantly affect a person's quality of life. One common symptom experienced by patients with mental disorders is auditory hallucination. Dhikr therapy is a non-pharmacological approach that can be used to help patients with auditory hallucinations. This case study aims to assist patients in reducing the level of auditory hallucinations using dhikr therapy. Methods: This research employed a case study with a descriptive-narrative method through a mental health nursing process approach involving one patient with auditory hallucinations at the Mental Health Service Unit of the Candipuro Community Health Center from June 11–13, 2024. The intervention included nursing actions that involved dhikr therapy conducted for three days with a duration of 10–20 minutes per session. Data analysis was performed by observing changes in the level of hallucinations before and after dhikr therapy. Results: The implementation of dhikr therapy for three days showed a reduction in auditory hallucinations and an improvement in sensory perception criteria. The patient rarely heard whispers, sensory distortions decreased, patient responses improved, and behaviors indicating the perception of hearing voices diminished. The AHRS questionnaire results indicated the effectiveness of dhikr therapy in reducing auditory hallucinations, with a final score of 17, categorizing it as moderate hallucination. Conclusions: Based on the results of this case study, it is hoped that nurses can provide dhikr therapy as a non-pharmacological treatment option for patients with mental disorders experiencing auditory hallucinations. This research is also expected to be developed further by applying dhikr therapy to multiple patients with similar cases for comparative analysis.